The Relationship between Social Interaction and Interpersonal Communication in Class X-XI Students at UPGRIS Laboratory High School - Nadhifa Yumna Salsabila (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the relationship between social interaction and interpersonal communication in class X-XI SMA Laboratory UPGRIS. The results of the correlation test in this study using the Pearson product moment correlation test, obtained a significance result of (r) = 0.894. While the r table value for a total sample of 82 with a significance level of 5% is 0.21, which means that the two variables have a significant relationship. The results show that there is a relationship between social interaction and interpersonal communication in students of class X-XI SMA Laboratory UPGRIS. Based on this research, it is hoped that students will further improve interpersonal communication skills by fostering social interaction and social contact.